Predictive factors for successful external cephalic version with regional anesthesia. Issue 5 (16th February 2023) - Unno, Saori; Ogawa, Kohei; Nukariya, Akinori; Umehara, Nagayoshi; Sago, Haruhiko
Abstract: Aim: We aimed to investigate predictive factors of successful external cephalic version (ECV) using regional anesthesia. Methods: In this retrospective study, we included women who underwent ECV at our center from 2010 to 2022. The procedure had been conducted using regional anesthesia and the administration of intravenous ritodrine hydrochloride. The primary outcome was the success of ECV, which was defined as the rotation from a non‐cephalic to a cephalic presentation. Primary exposures were maternal demographic factors and ultrasound findings at ECV. To determine predictive factors, we conducted a logistic regression analysis. Results: Of 622 pregnant women who underwent ECV, missing data on any variables ( n  = 14) were excluded and the remaining 608 were analyzed. The success rate during the study period was 76.3%. Multiparous women had significantly higher success rates than primiparous women (adjusted odds ratio [OR]: 2.06 [95% confidence interval (CI): 1.31–3.25]). Women with a maximum vertical pocket (MVP) of <4 cm had significantly lower success rates than those with 4 cm < MVP ≤6 cm (OR: 0.56 [95% CI: 0.37–0.86]). The non‐anterior placental location was associated with higher success rates than the anterior placental location (OR: 1.46 [95% CI: 1.00–2.17]). Conclusions: Multiparity, MVP >4 cm, and non‐anterior placental locations were associated with successful ECV. These three factors could be useful for patient selection for successful ECV.